Literature Review: Risk Factors for Obesity in Adolescents - Filistea Winda Emilia; Meitria Syahadatina Noor; Harapan Parlindungan Ringoringo; Eko Suhartono; Herawati Herawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Adolescent obesity is a significant global health problem that can persist into adulthood and lead to various degenerative diseases such as hypertension, coronary heart disease, and type 2 diabetes mellitus. The prevalence of obesity among adolescents in Indonesia is quite high, with 2018 Basic Health Research (Riskesdas) data showing that 31.0% of 15-year-olds suffer from central obesity. The high rates are often associated with multifactorial causes, including both genetic and external factors such as disproportionate dietary patterns and a lack of physical activity. Objective to analyze the relationship between various lifestyle factors such as diet, physical activity, sleep duration, and screen time with the incidence of obesity in adolescents using the literature review method. The review shows that unhealthy dietary patterns, such as the consumption of junk food and fast food, as well as excess energy intake, have a significant relationship with the incidence of obesity. Additionally, a lack of physical activity is proven to be a dominant risk factor. Concurrently, an increase in screen time is identified as having a strong relationship with obesity, as it reduces time for physical activity. Findings from one of the journals also show that peer influence has a significant correlation with junk food consumption behavior in adolescents, which can ultimately affect their nutritional status. The incidence of obesity in adolescents is a multifactorial problem that is highly influenced by a combination of poor dietary habits, a lack of physical activity, a sedentary lifestyle as measured by screen time, and social factors such as peer influence. Interventions to address obesity must be comprehensive, focusing not only on the individual but also on their social environment.